Lead‐Free Solar Cells based on Tin Halide Perovskite Films with High Coverage and Improved Aggregation. Issue 40 (5th September 2018) - Liu, Jiewei; Ozaki, Masashi; Yakumaru, Shinya; Handa, Taketo; Nishikubo, Ryosuke; Kanemitsu, Yoshihiko; Saeki, Akinori; Murata, Yasujiro; Murdey, Richard; Wakamiya, Atsushi
Abstract: Two simple methods to improve tin halide perovskite film structure are introduced, aimed at increasing the power conversion efficiency of lead free perovskite solar cells. First, a hot antisolvent treatment (HAT) was found to increase the film coverage and prevent electrical shunting in the photovoltaic device. Second, it was discovered that annealing under a low partial pressure of dimethyl sulfoxide vapor increased the average crystallite size. The topographical and electrical qualities of the perovskite films are substantively improved as a result of the combined treatments, facilitating the fabrication of tin‐based perovskite solar cell devices with power conversion efficiencies of over 7 %. Abstract : Two simple methods, hot antisolvent treatment (HAT) and low partial pressure solvent vapor treatment, are introduced to modify the preparation process of tin halide perovskite films. These treatments significantly improve the film quality and enhance the photovoltaic performance of tin‐based perovskite solar cells.